Value chain and marketing practices for Pineapple (Ananas comosus) in Kerala - Rai, Apeksha K.; Parayil, Chitra; M., Divya K. (Journal of Tropical Agriculture, 2023)
The study analyses the value chain in pineapple and examines the degree of value addition among different value chain actors. Also finds the factors that affect the competitiveness of the value chain in the study area. The study was conducted in the Ernakulam district of Kerala. Simple statistical tools were used for the analysis of primary data collected from 120 respondents. The study revealed that marketing channels for fresh and processed pineapple were well established and were dominated by traders. Value chain analysis shows that value addition was least at the farm level and was highest at the processor stage. The factors affecting competitiveness were identified and strategies to upgrade the value chain were proposed. The study suggested that the adoption of good management practices and the provision of improved infrastructure facilities would enable farmers to fetch a higher price for their produce.